A comparative study of oral nifedipine and intravenous labetalol in control of acute hypertension in severe pre-eclampsia and eclampsia - Gavit, Yogita; Sharma, Deepika; Dixit, Pratibha V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: This study was conducted to compare oral Nifedipine and intravenous Labetalol in control of acute hypertension in severe pre-eclampsia and eclampsia. This study was observational study with 80 sample size in which 40 sample size treated with intravenous Labetalol and other 40 sample size treated with oral Nifedipine. The maternal and perinatal outcome in two groups sample size with oral Nifedipine and intravenous Labetalol compared and found that nevertheless these results do establish oral Nifedipine as an alternative to IV Labetalol in lowering BP in acute severe hypertension. In summary oral Nifedipine may be preferable as it has a convenient dosing pattern orally. Methods: The present study was conducted in tertiary care centre Mumbai from June 2016 to October 2016. All pregnant woman diagnosed with acute hypertension in severe pre-eclampsia and eclampsia in labour room were enrolled in the study. Results: In the present study oral Nifedipine as an alternative to IV Labetalol in lowering BP in acute severe hypertension. In summary oral Nifedipine may be preferable as it has a convenient dosing pattern orally. Conclusions: A hypertensive disorder of pregnancy is one of the life-threatening complication encountered in obstetrics and globally is major cause of maternal morbidity and mortality. Management of acute severe hypertension in pregnancy is a challenging task. Present study compares the efficacy of oral Nifedipine and IV Labetalol in reaching the therapeutic goal. From the results of this study we can well conclude that oral Nifedipine is more efficacious.